Five surprises about the physics of time - Martin-Dussaud, Pierre (BACHELARD STUDIES - ÉTUDES BACHELARDIENNES - STUDI BACHELARDIANI, 2024)
Over the past centuries, significant advancements have been made in our understanding of time, including its measurement and nature. These advancements have been propelled by conceptual breakthroughs facilitated by technical progress. For the formation of their scientific mind, physicists must transcend their initial preconceptions about time and are led to retrace the historical milestones to rediscover the concept of time at various levels of intricacy. Drawing inspiration from my own journey as a student and researcher, this article will explore five pivotal moments that were intellectual surprises and shaped my subsequent pursuit of comprehending time.